Feedstock-dependent nutrient retention and release mechanisms of manure-derived biochars: Implications for mitigating agricultural nutrient loss - Peiyu Luo; Chaoqun Wei; Jing Wang; Kozo Ueda; Xu Yang; Xiaori Han; Jun Meng (Journal of Environmental Management, 2026)

High-turbidity bottom mixed-layer water on the shelf off Hokkaido in the Okhotsk Sea: distribution, seasonal variations, and spreading - Tomohiro Nakamura; Junki Ueda; Tokihiro Kono; Jun Nishioka; Humio Mitsudera; Kaoru Ito (Journal of Oceanography, 2025)

Validating knowledge-based volumetric modulated arc therapy plans with a multi-institution model (broad model) using a complete open-loop dataset for prostate cancer - Takaaki Ito; Kazuki Kubo; Ryuta Nakahara; Jun-ichi Fukunaga; Yoshihiro Ueda; Tatsuya Kamima; Yumiko Shimizu; Makoto Hirata; Ryu Kawamorita; Kentaro Ishii; Kiyoshi Nakamatsu; Hajime Monzen (Physical and Engineering Sciences in Medicine, 2025)

Longitudinal structuring of stream-fish assemblages: is niche partitioning observed in two-species systems applicable to three-species systems? - Kentaro Morita; Jun-ichi Tsuboi; Genki Sahashi; Ryo Futamura; Kazutoshi Ueda; Mari Kuroki (Ichthyological Research, 2024)
Longitudinal distribution and niche partitioning phenomena have been extensively reported for streams containing two salmonid species but remain poorly understood for streams containing three or more salmonid species. Herein, we examined the abiotic environmental variables and population densities of fishes, including three salmonids, in 30 reaches of the Setose River, Hokkaido, Japan, across altitudes (120–450 m) and maximum water temperature (15–26 °C) gradients to determine the distribution of major fish species in this system. The densities of white-spotted charr Salvelinus leucomaenis , southern Asian Dolly Varden Salvelinus curilus , masu salmon Oncorhynchus masou , fluvial sculpin Cottus nozawae , and stone loach Barbatula oreas varied along environmental gradients despite their wide distribution sympatrically. We further investigated the interspecific interactions between three potentially competitive salmonids, white-spotted charr, Dolly Varden, and masu salmon. We observed that in the three-species system, including upstream Dolly Varden, salmon occupied upstream areas colder than those inhabited by charr, which is contrary to the pattern reported for charr and salmon two-species systems, wherein charr are found in the colder upstream areas. In underwater observations, salmon preferred faster water velocities than charr and Dolly Varden. Dolly Varden were found exclusively on the riverbed, followed by charr, whereas salmon occurred further away from the riverbed. Analysis of the stomach contents revealed that all three salmonids depended on terrestrial insects, but only Dolly Varden consumed benthic aquatic insects. In our three-species system that included Dolly Varden (preadapted to benthos foraging), no difference was observed in the degree of terrestrial insect consumption between charr and salmon. These results are in striking contrast to the reports of charr preying on relatively more aquatic insects than those consumed by salmon in charr and salmon two-species systems. Therefore, we speculate that Dolly Varden and salmon influence interspecific interactions between charr and salmon and between charr and Dolly Varden, respectively, explaining the distinct longitudinal distribution and feeding habits observed in two- vs. three-species systems. These variant interspecific interactions among the three competing species may have driven the expansion of their sympatric zones.

Visualizing histone H4K20me1 in knock-in mice expressing the mCherry-tagged modification-specific intracellular antibody - Yuko Sato; Maoko Takenoshita; Miku Ueoka; Jun Ueda; Kazuo Yamagata; Hiroshi Kimura (Histochemistry and Cell Biology, 2024)
During development and differentiation, histone modifications dynamically change locally and globally, associated with transcriptional regulation, DNA replication and repair, and chromosome condensation. The level of histone H4 Lys20 monomethylation (H4K20me1) increases during the G2 to M phases of the cell cycle and is enriched in facultative heterochromatin, such as inactive X chromosomes in cycling cells. To track the dynamic changes of H4K20me1 in living cells, we have developed a genetically encoded modification-specific intracellular antibody (mintbody) probe that specifically binds to the modification. Here, we report the generation of knock-in mice in which the coding sequence of the mCherry-tagged version of the H4K20me1-mintbody is inserted into the Rosa26 locus. The knock-in mice, which ubiquitously expressed the H4K20me1-mintbody, developed normally and were fertile, indicating that the expression of the probe does not disturb the cell growth, development, or differentiation. Various tissues isolated from the knock-in mice exhibited nuclear fluorescence without the need for fixation. The H4K20me1-mintbody was enriched in inactive X chromosomes in developing embryos and in XY bodies during spermatogenesis. The knock-in mice will be useful for the histochemical analysis of H4K20me1 in any cell types.

Standardization of knowledge-based volumetric modulated arc therapy planning with a multi-institution model (broad model) to improve prostate cancer treatment quality - Yoshihiro Ueda; Jun-ichi Fukunaga; Tatsuya Kamima; Yumiko Shimizu; Kazuki Kubo; Hiroshi Doi; Hajime Monzen (Physical and Engineering Sciences in Medicine, 2023)

Genetic diversification of the Kanehira bitterling Acheilognathus rhombeus inferred from mitochondrial DNA , with comments on the phylogenetic relationship with its sister species Acheilognathus barbatulus - Takuya Miyake; Jun Nakajima; Keitaro Umemura; Norio Onikura; Takayoshi Ueda; Carl Smith; Kouichi Kawamura (Journal of Fish Biology, 2021)
The Kanehira bitterling, Acheilognathus rhombeus , is a freshwater fish, discontinuously distributed in western Japan and the Korean Peninsula. Unusually among bitterling it is an autumn‐spawning species and shows developmental diapause. Consequently, the characterization of its evolutionary history is significant not only in the context of the fish assemblage of East Asia, but also for understanding life‐history evolution. This study aimed to investigate the phylogeography of A. rhombeus and its sister species Acheilognathus barbatulus , distributed in China, using a mitochondrial analysis of the ND1 gene from 311 samples collected from 50 localities in Japan and continental Asia. Phylogenetic analysis revealed that A. barbatulus is included in A. rhombeus and genetically closer to Japanese A. rhombeus than to Korean A. rhombeus . Divergence of Korean A. rhombeus and A. barbatulus from Japanese A. rhombeus was estimated to be from the late Pliocene (3.44 Mya) and the early Pleistocene (1.98 Mya), respectively. Each event closely coincided with the time of the Japan Sea opening. Japanese A. rhombeus comprised seven lineages: three in Honshu and four in Kyushu. One lineage in central Kyushu was genetically closer to the Honshu lineages than to other lineages in northern Kyushu. Divergence of Japanese lineages was estimated to be from the early to middle Pleistocene (0.55–0.93 Mya), during a period of geological and paleoclimatic change, including volcanic activity. Population expansion in the late Pleistocene ( A. rhombeus / A. barbatulus was likely to have repeatedly colonized Japan from the continent through land bridges in the late Pliocene and the early Pleistocene. However, the close genetic relationship between Japanese A. rhombeus and A. barbatulus suggests another possibility, with the second colonization occurring in reverse, from Japan to China. The small genetic distance between them indicates that the colonization occurred later than colonization events of other freshwater fishes, including other bitterling species.

Biomonitoring method for neonicotinoid insecticides in urine of non-toilet-trained children using LC-MS/MS - Jun Ueyama; Arisa Aoi; Yuko Ueda; Naoko Oya; Yuka Sugiura; Yuki Ito; Takeshi Ebara; Michihiro Kamijima (Food Additives & Contaminants: Part A, 2020)

Anti-phase cocontraction practice attenuates in-phase low-frequency oscillations between antagonistic muscles as assessed with phase coherence - Nayef E. Ahmar; Jun Ueda; Minoru Shinohara (Experimental Brain Research, 2020)

Effects of processing and cooking on the reduction of dinotefuran concentration in Japanese rice samples - Minae Watanabe; Jun Ueyama; Eiji Ueno; Yuko Ueda; Masaya Oda; Yuko Umemura; Takashi Tanahashi; Yoshitomo Ikai; Isao Saito (Food Additives & Contaminants: Part A, 2018)

Tip-cell behavior is regulated by transcription factor FoxO1 under hypoxic conditions in developing mouse retinas - Moe Fukumoto; Kanako Kondo; Kazumasa Uni; Tomoko Ishiguro; Mikiko Hayashi; Shinnosuke Ueda; Itsuki Mori; Kenta Niimi; Fumi Tashiro; Satsuki Miyazaki; Jun-Ichi Miyazaki; Shinobu Inagaki; et al. (Angiogenesis, 2018)

Enzymatic activities for lignin monomer intermediates highlight the biosynthetic pathway of syringyl monomers in Robinia pseudoacacia - Jun Shigeto; Yukie Ueda; Shinya Sasaki; Koki Fujita; Yuji Tsutsumi (Journal of Plant Research, 2017)

A Mechanism Enhancing Macromolecule Transport Through Paracellular Spaces Induced by Poly-L-Arginine: Poly-L-Arginine Induces the Internalization of Tight Junction Proteins via Clathrin-Mediated Endocytosis - Tsutomu Yamaki; Yusuke Kamiya; Kazuo Ohtake; Masaki Uchida; Toshinobu Seki; Hideo Ueda; Jun Kobayashi; Yasunori Morimoto; Hideshi Natsume (Pharmaceutical Research, 2014)

Purification and visualization of encephalomyocarditisvirus synthesized by an in vitro protein expression system derived from mammalian cell extract - Tominari Kobayashi; Jun Yukigai; Kosaku Ueda; Kodai Machida; Mamiko Masutani; Yuri Nishino; Atsuo Miyazawa; Hiroaki Imataka (Biotechnology Letters, 2013)

Sulfur deposition simulations over China, Japan, and Korea: a model intercomparison study for abating sulfur emission - Cheol-Hee Kim; Lim-Seok Chang; Fan Meng; Mizuo Kajino; Hiromasa Ueda; Yuanhang Zhang; Hye-Young Son; Jong-Jae Lee; Youjiang He; Jun Xu; Keiichi Sato; Tatsuya Sakurai; et al. (Environmental Science and Pollution Research, 2012)

Comparative Genetics of the Poly-Q Tract of Ataxin-1 and Its Binding Protein PQBP-1 - Tatsuaki Kurosaki; Jun Gojobori; Shintaroh Ueda (Biochemical Genetics, 2012)

Long-term simulations of the sulfur concentrations over the China, Japan and Korea: A model comparison study - Cheol-Hee Kim; Lim-Seok Chang; Jeong-Soo Kim; Fan Meng; Mizuo Kajino; Hiromasa Ueda; Yuanhang Zhang; Hye-Young Son; Youjiang He; Jun Xu; Keiichi Sato; Chang-Keun Song; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Two novel decanedienamide derivatives, JBIR-07 and -08, from Streptomyces versipellis 4083-SVS6 - Jun-ya Ueda; Motoki Takagi; Kazuo Shin-ya (Natural Product Research, 2009)

Transient receptor potential (TRP) protein 7 acts as a G protein-activated Ca2+ channel mediating angiotensin II-induced myocardial apoptosis - Shinji Satoh; Haruki Tanaka; Yasuko Ueda; Jun-ichi Oyama; Masahiro Sugano; Hideki Sumimoto; Yasuo Mori; Naoki Makino (Molecular and Cellular Biochemistry, 2007)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Glutamate excess and free radical formation during and following kainic acid-induced status epilepticus - Yuto Ueda; Hidekatsu Yokoyama; Akira Nakajima; Jun Tokumaru; Taku Doi; Yoshio Mitsuyama (Experimental Brain Research, 2002)

Characterization of the human nebulette gene: a polymorphism in an actin-binding motif is associated with nonfamilial idiopathic dilated cardiomyopathy - Takuro Arimura; Takeyuki Nakamura; Shitoshi Hiroi; Manatsu Satoh; Megumi Takahashi; Nobuhisa Ohbuchi; Kazuo Ueda; Tatsuhito Nouchi; Noriko Yamaguchi; Jun Akai; Akira Matsumori; Sigetake Sasayama; et al. (Human Genetics, 2000)

Kindling phenomena induced by the repeated short-term high potassium stimuli in the ventral hippocampus of rats: on-line monitoring of extracellular glutamate overflow - Yuto Ueda; Taku Doi; Jun Tokumaru; Yoshio Mitsuyama; L. James Willmore (Experimental Brain Research, 2000)

Planktonic cyclopoid copepods from small ponds in Kyushu, Japan. II. Subfamily Cyclopinae - Hiroshi Ueda; Teruo Ishida; Jun-ichi Imai (Hydrobiologia, 1997)

Experimental study on respiratory sensitivity to inhaled toluene diisocyanate - Jun Huang; Kohji Aoyama; Atsushi Ueda (Archives of Toxicology, 1993)

High level expression of isocitrate lyase gene of n-alkane-utilizing yeast Candida tropicalis in Sacchromyces cerevisiae - Keinosuke Oda; Haruyuki Atomi; Mitsuyoshi Ueda; Jun Kondo; Yutaka Teranishi; Atsuo Tanaka (Archives of Microbiology, 1991)

Immunological effects of toluene diisocyanate exposure on painters - Jun Huang; Xiang -pu Wang; Ben -mei Chen; Atsushi Ueda; Kohji Aoyama; Toshio Matsushita (Archives of Environmental Contamination and Toxicology, 1991)